Intra-monthly variability of some physiological and blood parameters in pigs under different environmental conditions. Issue 5 (3rd July 2020) - Saoca, Concetta; Rizzo, Maria; Pugliese, Michela; Monteverde, Vincenzo; Giudice, Elisabetta; Piccione, Giuseppe
ABSTRACT: The aim of this study was to investigate the impact of intra-monthly variability of some physiological and blood parameters in pigs under different environmental conditions. For this purpose, 10 pigs (five males and five females) coming from a Sicilian farm were used. On all animals, rectal temperature, respiratory rate and blood sampling were carried out every five days, at six-time points under different environmental conditions, for the whole month of July 2017. For each period, ambient temperature, the relative humidity and the temperature-humidity index (THI) were recorded. Blood samples were tested for haematological (RBC, WBC, Hb, Hct) and haematochemical (GLU, TRIG, CHOL, TP, ALB and CREA) analyses. Our results showed a statistically significant effect of time ( P < 0.05) on rectal temperature, haematological and haematochimical parameters. CREA and respiratory rate have not shown statistically significant effect of time. Our data indicate that the majority of parameters evaluated in the present study showed variations related to changes in environmental conditions and to high ambient temperature. These results provide information into the physiological responses of pigs to different environmental conditions and could be useful to optimize the husbandry practices and provide useful information for monitoring changes in the health status of pigs.